Liquidez inmediata de las Cooperativas de Ahorro y Crédito Cacpe Zamora Cia. Ltda y de Servidores Públicos, R.I. - Cochancela Ayala, María José (My University, 2019)
The research carried out examines the liquidity of Ecuadorian banks, as well as some exogenous factors that cause people and companies that have applied for loans to financial institutions to fall into arrears, directly affecting the liquidity of banks due to non-recovery of loans. granted, the inquiry develops through the analysis of two financial statements and with the help of the ratios the liquidity analyzed from these instruments. The Ecuadorian financial system is classified into two categories, group A formed by banks and group B by cooperatives and savings banks, mutuals, all have their activity defined by the Superintendency of banks and insurance and by the Economy System Popular and supportive The corporate purpose of the banks is to grant credit to the different sectors and in turn generate income from ordinary activities under this modality, which is why the interest charged on the main source of income is constituted. The results found indicate that liquidity in the financial sector is the basis for the full development and growth of a country, companies and individuals, when banks have financial health ie liquidity contribute to boost the economy.
La investigación desarrollada examina la liquidez de la banca ecuatoriana, además algunos factores exógenos que hacen que las personas y empresas que han solicitado préstamos a las instituciones financieras caigan en morosidad afectando de manera directa a la liquidez de los bancos por la no recuperación de los créditos concedidos, la indagación desarrolla a través del análisis de dos estados financieros y con la ayuda de los ratios la liquidez analizada desde estos instrumentos. El sistema financiero ecuatoriano se encuentra clasificado en dos categorías, el grupo A conformado por los bancos y el grupo B por las cooperativas y cajas de ahorros, mutualistas, todas tienen su actividad definida por la Superintendencia de bancos y seguro y por el Sistema de Economía Popular y solidaria. El objeto social de los bancos es conceder crédito a los distintos sectores y a su vez generar ingresos de actividades ordinarias bajo esta modalidad por lo que se constituyen los intereses que cobran en la principal fuente de ingresos. Los resultados encontrados nos indican que la liquidez en el sector financiero es la base para el pleno desarrollo y crecimiento de un país, empresas y personas, cuando los bancos poseen salud financiera es decir liquidez contribuyen a dinamizar la economía.
Keywords: SECTOR FINANCIERO; ÍNDICE DE LIQUIDEZ; CRÉDITO; SOLVENCIA